Computed Tomography evaluation of maxillofacial injuries - Prasad, V Natraj; Khanal, Ashish (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The maxillofacial region, a complex anatomical structure, can be evaluated by conventional (plain) films, Tomography, Multidetector Computed Tomography, Three-Dimensional Computed Tomography, Orthopantomogram and Magnetic Resonance Imaging. The study was conducted with objective of describing various forms of maxillofacial injuries, imaging features of different types of maxillofacial fractures and the advantage of using Three- Dimensional Computed Tomography reconstructed image. Materials & Methods: A hospital based cross-sectional study was conducted among 50 patients during April 2014 to September 2016 using Toshiba Aquilion Prime 160 slice Multi Detector Computed Tomography scanner. Results: The maxillofacial fractures were significantly higher in male population (88%) than female population (12 %). Road traffic accidents were the most common cause of injury others being physical assault and fall from height. It was most common in 31-40 years (26%) and 21-30 (24%) years age group. Maxillary sinus was the commonest fracture (36%) followed by nasal bone and zygomatic bone (30%), mandible and orbital bones (28%). Soft tissue swelling was the commonest associated finding. Three dimensional images (3 D) compared to the axial scans missed some fractures. However, the extension of the complex fracture lines and degree of displacement were more accurately assessed. Complex fractures found were Le fort (6%) and naso-orbito-ethmoid (4%) fractures. Conclusion: The proper evaluation of complex anatomy of the facial bones requires Multidetector Computed Tomography which offers excellent spatial resolution enabling multiplanar reformations and three dimensional reconstructions for enhanced diagnostic accuracy and surgical planning.